Do undergraduate Universiti Sains Islam Malaysia (USIM) students with adequate oral health literacy have better oral health status? - Azlan Jaafar; Normaliza Ab Malik; Aws Hashim Ali Al-Kadhim (USIM Press, 2024)
MJoSHT2020, Volume 7, Special Issue, eISSN: 2601-0003